Nivolumab-Induced Autoimmune Encephalitis in Two Patients with Lung Adenocarcinoma. (4th July 2018) - Shah, Suma; Dunn-Pirio, Anastasie; Luedke, Matthew; Morgenlander, Joel; Skeen, Mark; Eckstein, Christopher
Abstract : Immune checkpoint inhibitors have improved patient survival outcomes in a variety of advanced malignancies. However, they can cause a number of immune-related adverse effects (irAEs) through lymphocyte dysregulation. Central nervous system (CNS) irAEs are rare, but as the number of indications for checkpoint inhibitors increases, there has been emergence of CNS immune-mediated disease among cancer patients. Given the relatively recent recognition of checkpoint inhibitor CNS irAEs, there is no standard treatment, and prognosis is variable. Therefore, there is a great need for further study of checkpoint inhibitor-induced CNS irAEs. Here, we present two unique cases of nivolumab-induced autoimmune encephalitis in patients with non-small cell lung cancer and review the available literature.